1985
DOI: 10.1111/j.1749-6632.1985.tb11849.x
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis as an Inflammatory Process

Abstract: In this brief review, we have addressed the roles of the monocyte-macrophage in atherogenesis, with emphasis on the recruitment to the arterial wall. We have presented summary data on the SMC-derived chemoattractant protein and also on the temporal evolution of monocyte-derived macrophages into cholesteryl ester-rich foam cells. The concept of atheroma as an inflammatory process has also been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Furthermore, we identified that ALCAM expression was up-regulated in the atherosclerotic aorta from apo-E knock-out mouse (data not shown). Given that inflammation plays crucial roles in atherosclerosis, ALCAM and sALCAM may play particular roles in the development of atherosclerosis (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified that ALCAM expression was up-regulated in the atherosclerotic aorta from apo-E knock-out mouse (data not shown). Given that inflammation plays crucial roles in atherosclerosis, ALCAM and sALCAM may play particular roles in the development of atherosclerosis (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, many reports have suggested that hyperinsulinemia associated with insulin resistance might be a risk factor in atherosclerotic diseases such as coronary heart disease (9 -11), which is one of the major causes of death in such patients (34). Macrophages play an important role in the initial stages of atherosclerosis by taking up modified low density lipoprotein, which is accompanied by a morphological change into foam cells and secretion of various cytokines (4,35,36). In addition, many cholesterol-enriched foam cells have been observed to be a characteristic aspect of the developed atherosclerotic lesions (6).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are mediators of inflammation in the vasculature and participate in the development of atherosclerotic plaques [Schwartz et al, 1985]. In the pathogenesis of atherosclerosis, PPARα activation could result initially in reduced leukocyte adhesion to activated endothelial cells of the arterial lumen, and subsequently in inhibiting the formation of macrophage foam cells by regulating expression of genes involved in reverse cholesterol transport and reactive oxygen species output [Chinetti et al, 2001; Zandbergen and Plutzky, 2007].…”
Section: Pparα Functionsmentioning
confidence: 99%